Primary Amelanotic Melanoma of the Maxillary Gingiva: A Case Report - Sungkhao, Wipasinee; Klanrit, Poramaporn; Jinaporntham, Suthin; Subarnbhesaj, Ajiravudh (UI Scholars Hub, 2019)
Malignant melanoma arising in the oral cavity is particularly rare. The clinical presentations of malignant melanoma can range from a benign-looking pigmented macule or nodule to a non-pigmented neoplasm which can be categorized into primary or metastatic lesions. Less than 2% of all melanomas show no pigmentation and could lead to misdiagnosis. Objective: To present a benign looking but life-threatening malignancy of melanotic melanoma. Case report: A 59-year-old female patient was referred to a regional hospital for further treatment of a localized gingival swelling with no ulceration at the anterior maxilla. An incisional biopsy was performed, with initial histopathologic result of a peripheral giant cell granuloma. CT images demonstrated a locally invasive bone destruction compromising the buccal cortical plate. The second biopsy revealed a non- demarcated mass consisting of spindle-shaped to ovoid cells of variable sizes, shapes and staining characteristics, forming short fascicles of various directions in hyalinized and myxoid stroma with focal areas of necrosis, bone invasion and infiltration of vascular wall. The tumor cells strongly expressed Vimentin, S-100, HMB- 45 and Melan-A and the diagnosis of amelanotic melanoma was finally made. Conclusion: Oral amelanotic melanoma is extremely rare and difficult to diagnose because of the absence of melanin pigment. Immunohistochemistr y is a significant tool being used to establish the correct diagnosis.